IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY SEBAGAI MODAL SOSIAL PADA PT PLN (PERSERO) DISTRIBUSI JATIM SURABAYA - Rafika, Dwi Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out and to analyze the implementation of Corporate Social Responsibility as social capital which is carried out by PT PLN (Persero) Surabaya East Java Distribution through partnership and community development program. The research has found that PT PLN (Persero) Surabaya East Java Distribution since 2010 has not totally carried out the partnership program, but only the community development program. The arising problems are lacking of coordination and communication and the lack of supervision and the coach of community development. It is expected that the related parties can improve their coordination, and form a special team for the effectiveness of supervision outside the head office. From activity responsibility, PT PLN (Persero) has arranged Sustainability Report since 2010. PT PLN (Persero), from this report, has presented quality reporting in accordance with the stakeholdersâ information need, develop its social responsibility in order to achieve sustainability development which synergizes environment, social, and business performance.Keywords: Corporate Social Responsibility, Partnership and Community Development Program, Sustainability Report, Sustainability Development.